Examining the Link between Employee Job Satisfaction and Commitment at the Prevention and Combating of Corruption Bureau in Tanzania - Kalachishvili, Mariam (Journal of Global Economy, Business and Finance, 2025)
The aim of this study was to examine the relationship between employee job satisfaction and commitment to the Prevention and Combating of corruption Bureau in Tanzania. Job satisfaction is an integral part of organizational performance. The level of job satisfaction has relation with various aspects of work behavior such as organizational commitment. This research was carried out among the selected PCCB employees at different levels of organization’s structure and locus. A quantitative method was used to gather relevant information regarding the relationship between job satisfaction and organization commitment. The result revealed that all six job satisfaction facets are correlated with job satisfaction. The result can be used as a guiding method for the PCCB management to increase their employees’ commitment. Job satisfaction has a positive relation with employee commitment if employees are satisfied, they are organizationally committed we found that job satisfaction has a positive impact on employee commitment.